Life in an Alpha Territory: Discontinuity and conflict in an elite London 'village'. (November 2016) - Webber, Richard; Burrows, Roger
This paper forms part of a larger study of the social implications of London becoming the location of choice for the global 'super-rich'. The study examines how members of new wealth elites organise their day-to-day activities, the impact their growing numbers have on the prestigious neighbourhoods from which they are displacing pre-existing elites, and the disruptive effect they have on previously taken-for-granted mores, networks and places of association. The aim of the paper is to situate this wider study within a geographic and historical context by framing it within the arguments of Piketty, namely that increased levels of inequality since 1980 are best understood not as a secular trend but as signifying a return to the pre-existing conditions that characterised Western society prior to 1914. To analyse the evolution of – what geodemographers have termed – the Alpha Territory in London over a period of 500 years the paper takes Highgate Village as a case study area, identifies the manner in which the Village's varied housing stock appeals to different manifestations of this Alpha Territory and uses three recent planning disputes to bring to the surface otherwise hidden conflicts between the interests of global capital and the defenders of more traditional elite values. Returning to the issues raised by Piketty, the paper concludes with an analysis of social change through the use of archive material which enables the lifestyles of those who currently occupy Highgate's most prestigious properties to be compared with those who occupied them a hundred years ago.